Influencing Factors and Cumulative Risk Analysis of Cervical Lymph Node Metastasis of Papillary Thyroid Microcarcinoma - Yin, Yirong; Xu, Xiang; Shen, Liyan; Zhao, Wenjuan; Diao, Hongcui; Li, Chengqian (Frontiers in Oncology, 2021)
Objective To explore the influencing factors and cumulative risk of lymph node metastasis (LNM) in papillary thyroid microcarcinoma (PTMC) patients. Methods 607 patients confirmed PTMC pathologically after thyroidectomy were enrolled in this retrospective study. The rate of LNM was calculated. Different clinicopathological characteristics were compared in PTMC patients with and without LNM and in different subgroups of LNM, respectively. Correlation between clinicopathological characteristics and LNM was analyzed and the cumulative risk of LNM according to different clinicopathological characteristics was calculated. Results (1) There were 228 cases (37.56%) of PTMC combined with LNM. Compared with the non-lymph node metastasis group, the proportion of age <55 years, male, multiple foci, bilateral foci, diameter>0.5cm, extracapsular invasion, HT and intermediate-to-high risk stratification for recurrence of the LNM group was significantly increased (all p<0.05);(2) Multivariate logistic regression analysis showed that age <55years, male, multiple foci, diameter>0.5cm,HT were independently positively correlated with LNM (all p <0.05); (3) Subgroup analysis showed that women aged <55 years combined with HT and aged≥55 years combined with BMI≥25 kg/m2 were independently positively associated with LNM; (4) With the increase of the tumor diameter, the cumulative risk of LNM in group of age <55 years, males, and multiple foci increased gradually, and was higher than those of age≥55 years, females and single foci, respectively. (5) Among the 228 cases of LNM, the proportion of lymph nodes (LN) >5 and the positive rate of LN were both higher in male group than that in the female group. The proportion of multiple foci and HT in LLNM group was higher than that in CLNM group (all P<0.05). Conclusion Age <55 years, males, multiple foci, diameter >0.5cm and HT were independent risk factors of LNM; HT was an independent risk factor for LNM in female <55 years old, and BMI≥25 kg/m2 was an independent risk factor for LNM in female ≥55 years old; The increase of tumor diameter in age <55 years, males, multiple foci, and bilateral foci increased the cumulative risk of LNM, respectively; The number of LNM and the positive rate of LNM were both higher in male, and patients with multiple foci or HT were more likely to develop into LLNM.